Seni Pertunjukan Hadrah di Kota Medan Analisis Teknik Interloking dalam Ansambel Musik Perkusi Hadrah - Muhammad Habibur Ridho; Mauly Purba (Departement of Mathematics Education, 2024)
Hadrah is a traditional Islamic music performance art that integrates singing in the form of praises and veneration to the Prophet Muhammad SAW with accompaniment from a percussion music ensemble. Percussion instruments such as rebana, bedug, kecrek, and others play the main role in this performance. This research conducted in the city of Medan focuses on analyzing the specific playing techniques used in the hadrah percussion music ensemble, especially the interlocking technique where the rhythmic patterns played by each instrument interlock with one another, creating a distinctive rhythmic complexity that characterizes the hadrah performance art. Hadrah performances are usually held during Islamic religious celebrations such as the Prophet's Birthday, Isra' Mi'raj, religious study gatherings, and other commemorations. The interlocking technique in hadrah percussion music performances shows similarities with the way traditional Indonesian percussion instruments are played. This research employs an ethnographic approach relevant for observing, analyzing, and understanding the interlocking playing technique and the function of hadrah musical instruments within the context of Islamic religious performances and rituals in Indonesia, specifically in the city of Medan. Through direct observation, the researcher aims to capture the essence of the hadrah performance art as an expression of the cultural identity of the Muslim community in the city of Medan.